104 House Rules and Clean Kids: The down-low on Tobacco. (19th August 2020) - Zhang, Caseng; Hicks, Alex; Osornio-Vargas, Alvaro; Brennan, Lesley; Hicks, Matt; Hicks, Anne
Abstract: Background: Despite multiple published guidelines outlining the potential health risks caused by tobacco smoke, young children continue to be exposed to the detrimental effects of household smoking. Environmental factors also have the potential to influence levels of tobacco exposure in children. Many factors such as comfort can influence the decisions of smoking parents to smoke indoors, increasing potential harm for children. Understanding the correlation between various locations within the household and tobacco exposure is helpful in informing a harm reduction strategy for smokers. This project compared the location of reported tobacco use to detection of the nicotine byproduct cotinine in children's urine samples. Objectives: To determine the impact of smoking location on unintentional tobacco exposure in children. Design/Methods: This prospective cross-sectional study focused on children under age ten, since 13% of Canadian children in grades 6 and up have tried a cigarette at least once. Of 286 parents approached during a pediatrician visit, 231 agreed to complete an exposure questionnaire and 132 children were able to provide a urine sample during the visit. A standard ELISA assay was used to measure urine cotinine. Results: About half of the 31% of households that reported smoking had an indoor smoking ban. Some indoor smokers isolated their activity to the garage (56%). Of the 84 children with detectable urine cotinine, 62 lived in homes that reported smoking. This suggests that some children were exposed to tobacco smoke through other sources or the underestimation of potential tobacco exposure. Fifteen percent of children from smoking homes had cotinine levels similar to nonsmoking homes. Children of indoor smokers were more likely to have detectable cotinine than those of outdoor smokers. Conclusion: Roughly 50% of smokers with children have an indoor smoking ban as a harm reduction strategy. In our study, children of smokers with an indoor smoking ban were less likely to have detectable urine cotinine. Although not smoking is the best strategy, limiting smoking to outside is an optimal harm mitigation strategy. For families with indoor smokers, encouraging them to isolate smoking to a single space like the garage may decrease unintentional pediatric exposure.